Will artificial intelligence solve the human resource crisis in healthcare? - Bertalan Meskó; Gergely Hetényi; Zsuzsanna Győrffy (BMC, 2018)
Abstract Artificial intelligence (AI) has the potential to ease the human resources crisis in healthcare by facilitating diagnostics, decision-making, big data analytics and administration, among others. For this we must first tackle the technological, ethical and legal obstacles. The human resource crisis is widening worldwide, and it is obvious that it is not possible to provide care without workforce. How can disruptive technologies in healthcare help solve the variety of human resource problems? Will technology empower physicians or replace them? How can the medical curriculum, including post-graduate education prepare professionals for the meaningful use of technology? These questions have been growing for decades, and the promise of disruptive technologies filling them is imminent with digital health becoming widespread. Authors of this essay argue that AI might not only fill the human resources gap, but also raises ethical questions we need to deal with today. While there are even more questions to address, our stand is that AI is not meant to replace caregivers, but those who use AI will probably replace those who don't. And it is possible to prepare for that.